PWE-098 Mechanisms the Underlying Development of Chronic Inflammation in Inflammatory Bowel Disease: Defining the Role of the Rage Pathway Using Computational and Biological Analysis Strategies. (4th June 2013) - Bramhall, M; Han, N; Haggart, R; Wilson, J; Brass, A; Cruickshank, S
Abstract : Introduction: Inflammatory bowel disease (IBD) is a chronic inflammatory disease with an estimated annual cost to the NHS of £720 million. Patients typically present with established disease and this makes it difficult to determine the underlying aetiology: knowledge that would aid early diagnosis and treatment. Methods: To better define factors underlying the development of IBD that might be used as diagnostic aids for treatment/prevention of IBD we have analysed the early immune response in mice that will develop colitis using a validated infection model of colitis. Microarray analyses of colon tissue were conducted using the Puma and Tigre packages for Bioconductor to determine gene expression and investigate the transcription factor pathways involved. Results: Microarray analysis identified an early and rapid increase in expression of the receptor for advanced glycation end-products (RAGE) in colitic prone (susceptible) mice. In contrast, mice that clear the infection (resistant mice) had no increase in RAGE. In addition, the transcription factor analysis revealed a downregulation of colitic protective factors in the RAGE signalling pathway. Immunohistochemistry data showed high RAGE expression in the gut epithelium prior to the onset of colitis. Previous work from our group has shown that epithelial cells promote dendritic cell recruitment associated with resistance and clearance of parasite infection. In the colitis model, infection also induced the rapid recruitment of macrophages and dendritic cells (DC) into the gut and lymph nodes in resistant mice but not susceptible mice. By day 31 post-infection, resistant mice had resolved the infection and inflammation whereas susceptible mice had significantly higher immune cell accumulation and colitis. Current work is addressing the expression of RAGE blocking ligands and the regulation of RAGE in the guts of resistant and susceptible mice. Conclusion: RAGE has been associated with chronic IBD in patients however our data implicates RAGE in the development and propagation of IBD. We propose that the RAGE pathway is an early indicator of IBD and may be useful therapeutically and in determining efficacy of IBD therapy. Disclosure of Interest: M. Bramhall Grant/Research Support from: Epistem Ltd., N. Han: None Declared, R. Haggart: None Declared, J. Wilson: None Declared, A. Brass: None Declared, S. Cruickshank: None Declared.